PROFESSIONAL COMPETENCIES OF MUNICIPAL EMPLOYEES: DIAGNOSTICS AND QUALIFICATIONS - Koryakovtseva, Olga; Bugaychuk, Tatyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article is devoted to the problems of increasing the professional competence of municipal employees in the information society. The transformation of the traditional knowledge paradigm of education on the basis of the competency-based approach is emphasized, the psychological characteristics of the activities of today's municipal servants are identified, various aspects of the ideas of domestic science on competence and competencies are identified, the specificity of the direction of additional professional education is considered. The presented study consists in the psychological diagnosis of the professional competencies of municipal employees for the further use of the results in the targeted development and implementation of continuing education programs for the mentioned category of students. Particular attention is paid to the attitude of employees towards the formation of a civic identity as an important factor in the consolidation of society. The results of the study are graphically presented in diagrams and comments, indicate the need to adapt a modern employee to changing conditions, the development of a willingness to learn new knowledge and technologies for working with people, to actively participate in the development of civil society and to widely involve additional professional education systems in this process.